Interlayer-pore coordinated silicon-carbon composite negative electrode material and preparation method thereof
Patent Information
- Application Number
- CN202611336464.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-23
AI Technical Summary
单一碳基体性能局限,石墨基体导电性好但硅负载量低(<20%);
[0047]本发明的技术方案的有益效果如下:本发明提出了一种双相载体复合结构,通过结合石墨层间沉积与多孔碳孔道沉积的技术优势,实现高容量、低膨胀、高首效的统一,为下一代高能量密度锂离子电池提供核心材料支撑,具体如下:
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of silicon-based anode materials, and more specifically, relates to a silicon-carbon composite anode material with interlayer-pore synergy and its preparation method. Background Technology
[0002] As the most mainstream electrochemical energy storage system, lithium-ion batteries have become a core requirement for improving energy density in new energy vehicles, portable electronic devices, and large-scale energy storage systems. Traditional graphite anode materials have a theoretical specific capacity of only 372 mAh / g, approaching their theoretical limit and severely restricting further improvements in battery energy density. Silicon-based anode materials, due to their extremely high theoretical specific capacity (4200 mAh / g) and suitable lithium intercalation potential (approximately 0.4 V vs. Li), offer a significant advantage. + With its abundant natural reserves, silicon (Li₂O₃) is widely recognized as the next-generation anode material with the greatest potential for industrialization. However, silicon materials face enormous volume expansion (>300%) during charge and discharge, leading to problems such as electrode structure pulverization, repeated rupture and regeneration of the solid electrolyte interphase (SEI) film, and shedding of active materials, which seriously affect the cycle life and first-efficiency performance of the battery.
[0003] Currently, the industry mainly adopts three technical routes to solve the volume expansion problem of silicon-based anodes: Nanoscale silicon-carbon composite material: A composite material of nanoscale silicon particles and carbon matrix is prepared by mechanical ball milling, but problems such as uneven dispersion of nanoscale silicon and weak interfacial bonding exist. Carbon-coated silicon oxide materials (SiOx / C): utilize the relatively low volume expansion of silicon oxide (about 160%), but have low first-efficiency (typically <85%) and limited specific capacity (about 1500 mAh / g). Chemical vapor deposition silicon-carbon materials (CVD Si / C): Depositing nano-silicon on a porous carbon framework allows for precise control of the silicon nanostructure, achieving a balance between high silicon content and low expansion.
[0004] Among them, chemical vapor deposition (CVD) technology is considered the most promising technology route due to its strong process controllability, precise nanostructures, and high feasibility of large-scale production. However, existing CVD silicon-carbon material technologies still face two major challenges: The performance of a single carbon matrix is limited, while the graphite matrix has good electrical conductivity but low silicon loading (<20%). Porous carbon matrix has a high silicon loading (>40%), but the high specific surface area leads to a decrease in first efficiency (<85%). There is a challenge in balancing volume expansion rate and cycle stability. It is difficult to meet the requirements of low expansion (<20%) and long cycle (>500 times) at the same time with high silicon content.
[0005] Based on the above industry pain points, there is an urgent need to propose a silicon-carbon composite anode material and preparation method with interlayer-pore synergy. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by proposing a silicon-carbon composite anode material and its preparation method that combines interlayer and porous carbon deposition. This invention achieves a balance between high capacity, low expansion, and high initial efficiency by integrating the technical advantages of graphite interlayer deposition and porous carbon channel deposition.
[0007] To achieve the above objectives, the present invention provides a method for preparing a silicon-carbon composite anode material with interlayer-pore synergy, the method comprising the following steps: S1-1: After placing the graphite substrate in the first reactor, the first reactor is evacuated and then argon-oxygen mixed gas is introduced in sequence for plasma pretreatment. S1-2: After the plasma pretreatment is completed, a mixture of silicon source gas is introduced into the first reactor to perform low-temperature deposition, gradient heating and high-temperature deposition treatment in sequence. S1-3: After the high-temperature deposition process is completed, the first reactor is gradually cooled under a protective atmosphere and a mixed gas containing passivating gas is introduced into the first reactor for cooling and passivation treatment to obtain graphite interlayer silicon. S2-1: After placing the porous carbon matrix in the second reactor, the second reactor is evacuated and then a first carbon source mixed gas is introduced in sequence to perform a two-stage closed-pore pretreatment. S2-2: After the two-stage closed-hole pretreatment is completed, the second reactor is evacuated and argon-hydrogen mixed gas is introduced in sequence to carry out hydrogen plasma activation treatment. S2-3: After the hydrogen plasma activation treatment is completed, a mixture of the second silicon source gas is introduced into the second reactor to perform low-temperature infiltration, medium-temperature nucleation and high-temperature filling treatment in sequence; S2-4: After the high-temperature filling process is completed, a second carbon source mixed gas is introduced into the second reactor to perform in-situ passivation treatment and obtain porous carbon channel silicon. S3-1: Spray an organic solution containing carbon nanotubes into the mixture of graphite interlayer silicon and porous carbon channel silicon, stir and dry to obtain a conductive bridge network. S3-2: The conductive bridge network is sequentially coated with a soft carbon layer, a hard carbon layer, and a graphite layer using chemical vapor deposition to obtain the interlayer-channel synergistic silicon-carbon composite anode material.
[0008] According to the present invention, preferably, the graphite matrix is at least one of artificial graphite, flake graphite and mesophase carbon microspheres; the particle size of the graphite matrix is 5-50 μm, more preferably 10-30 μm, and even more preferably 15-25 μm.
[0009] According to the present invention, preferably, in the plasma pretreatment: The volume ratio of argon to oxygen in the argon-oxygen mixture is (8-95):1; the inlet flow rate of the argon-oxygen mixture is 0.5-5 L / min. The output power of the radio frequency power supply for plasma pretreatment is 100-1000W; The plasma pretreatment time is 5-30 minutes; The steady-state working pressure of the first reactor after the argon-oxygen mixture is introduced is 1-50 Pa.
[0010] Table 1 Plasma Pretreatment
[0011] According to the present invention, preferably, in the low-temperature deposition process: The first mixture containing silicon source gas is a mixture of silicon source gas and argon gas, and the volume content of silicon source gas is 1-10 vol% based on the total volume of the mixture of silicon source gas and argon gas; the inlet flow rate of the first mixture containing silicon source gas is 0.5-5 L / min. The low-temperature deposition treatment is performed at a temperature of 500-600℃ for a time of 30-120 minutes. The steady-state working pressure of the first reactor after the first mixture containing silicon source gas is introduced is 0.1-0.8 MPa.
[0012] In this invention, the low-temperature deposition process involves depositing silicon at a lower temperature to nucleate at the edges between graphite layers.
[0013] Table 2 Low-temperature deposition treatment
[0014] According to the present invention, preferably, in the gradient heating process, the heating rate is 1-5℃ / min.
[0015] According to the present invention, preferably, in the high-temperature deposition process: The first mixture containing silicon source gas is a mixture of silicon source gas, hydrogen and argon, and based on the total volume of the mixture, the volume content of silicon source gas is 10-25 vol%, and the volume content of hydrogen is 0-15 vol%; the inlet flow rate of the first mixture containing silicon source gas is 0.5-5 L / min. The high-temperature deposition treatment is performed at a temperature of 600-750℃ for a time of 60-240 minutes. The steady-state working pressure of the first reactor after the first mixture containing silicon source gas is introduced is 0.05-0.5 MPa.
[0016] In this invention, after the low-temperature deposition treatment, the temperature is raised to a higher temperature at a certain rate for high-temperature deposition treatment, and then switched to a high-concentration silicon source gas for main deposition.
[0017] Table 3 High-temperature deposition treatment
[0018] According to the present invention, preferably, the silicon source gas used in the low-temperature deposition process and the high-temperature deposition process is each independently at least one of SiH4, SiH4 (silane), Si2H6 (disilane), SiCl4 (silicon tetrachloride), SiHCl3 (trichlorosilane), and SiH2Cl2 (dichlorosilane).
[0019] According to the present invention, preferably, in the cooling passivation treatment: The cooling rate of the gradient cooling is 1-15℃ / min, and the final temperature of the gradient cooling is 20-30℃. The passivating gas mixture is a mixture of argon and ethylene, and the volume content of ethylene is 0.5-5 vol% based on the total volume of the argon and ethylene mixture; the inlet flow rate of the passivating gas mixture is 0.5-5 L / min.
[0020] In this invention, the cooling passivation process includes: cooling under a nitrogen protective atmosphere and introducing a passivation gas (ethylene) to form an extremely thin protective layer on the surface of silicon particles.
[0021] Table 4 Cooling and passivation treatment
[0022] According to the present invention, preferably, the interlayer silicon in the graphite is silicon particles embedded in graphite sheets, wherein the particle size of the silicon particles is 20-50 nm, and the interlayer spacing of the graphite sheets after the silicon particles are embedded is 0.45-0.55 nm.
[0023] According to the present invention, preferably, the porous carbon matrix is coconut shell-based porous carbon and / or rice husk-based porous carbon; the BET specific surface area of the porous carbon matrix is 1500-2500 m². 2 / g.
[0024] According to the present invention, preferably, in the two-stage closed-cell pretreatment: The pressure inside the second reactor is ≤50Pa after evacuation. The two-stage closed-pore pretreatment includes a first-stage closed-pore pretreatment and a second-stage closed-pore pretreatment performed sequentially. In the first-stage closed-cell pretreatment: The first carbon source mixture is a mixture of acetylene and nitrogen, with a volume ratio of acetylene to nitrogen of 1:(2-10); the inlet flow rate of the first carbon source mixture is 0.5-5 L / min. The temperature of the first-stage closed-cell pretreatment is 600-750℃, and the time is 0.5-3h; In the secondary closed-cell pretreatment: The first carbon source mixture is a mixture of methane and hydrogen, with a volume ratio of methane to hydrogen of 1:(1-5); the inlet flow rate of the first carbon source mixture is 0.5-5 L / min. The temperature of the secondary closed-pore pretreatment is 700-850℃, and the time is 0.2-1.5h.
[0025] In this invention, the tiny ineffective pores of a porous carbon matrix can be sealed by a two-stage pore-closing pretreatment (i.e., two-stage chemical vapor deposition).
[0026] Table 5 Two-stage closed-cell pretreatment
[0027] According to the present invention, preferably, in the hydrogen plasma activation treatment: The volume ratio of argon to hydrogen in the argon-hydrogen mixture is 1:(1-9); the inlet flow rate of the argon-hydrogen mixture is 0.5-5 L / min. The output power of the radio frequency power supply for hydrogen plasma activation treatment is 100-1000W; The hydrogen plasma activation treatment time is 5-60 min; The steady-state working pressure of the second reactor after the argon-hydrogen mixture is introduced is 20-100 Pa.
[0028] In this invention, the surface wettability is improved by the hydrogen plasma activation treatment, so that the silicon source gas can be uniformly introduced into all the channels.
[0029] Table 6 Hydrogen plasma activation treatment
[0030] According to the present invention, preferably, in the low-temperature permeation treatment: The second mixture containing silicon source gas is a mixture of silicon source gas and hydrogen, and the volume content of silicon source gas is 5-15 vol% based on the total volume of the mixture of silicon source gas and hydrogen; the inlet flow rate of the second mixture containing silicon source gas is 0.5-5 L / min. The low-temperature permeation treatment is performed at a temperature of 600-700℃ for a time of 0.5-2 hours.
[0031] According to the present invention, preferably, in the mesophilic nucleation process: The second mixture containing silicon source gas is a mixture of silicon source gas, hydrogen chloride, and hydrogen, and based on the total volume of the mixture of silicon source gas, hydrogen chloride, and hydrogen, the volume content of silicon source gas is 15-25 vol%, and the volume content of hydrogen chloride is 2-8 vol%; the inlet flow rate of the second mixture containing silicon source gas is 0.5-5 L / min. The intermediate-temperature nucleation treatment is performed at a temperature of 700-800℃ for 1-3 hours.
[0032] According to the present invention, preferably, in the high-temperature filling process: The second mixture containing silicon source gas is a mixture of silicon source gas and hydrogen, and the volume content of silicon source gas is 25-40 vol% based on the total volume of the mixture of silicon source gas and hydrogen; the inlet flow rate of the second mixture containing silicon source gas is 0.5-5 L / min. The high-temperature filling treatment is carried out at a temperature of 800-900℃ for a time of 0.5-2 hours.
[0033] Table 7 Low-temperature infiltration treatment, intermediate-temperature nucleation treatment, and high-temperature filling treatment
[0034] According to the present invention, preferably, the silicon source gas used in the low-temperature infiltration treatment, the medium-temperature nucleation treatment and the high-temperature filling treatment is each independently at least one of SiH4, SiH4, Si2H6, SiCl4, SiHCl3 and SiH2Cl2.
[0035] According to the present invention, preferably, in the in-situ passivation treatment (in-situ carbon coating): The second carbon source mixture is a mixture of ethylene and hydrogen, and the volume content of ethylene is 2-10 vol% based on the total volume of the mixture of ethylene and hydrogen; the inlet flow rate of the second carbon source mixture is 0.5-5 L / min. The in-situ passivation treatment is performed at a temperature of 650-800℃ for 15-90 minutes.
[0036] Table 8 In-situ passivation treatment
[0037] According to the present invention, preferably, the porous carbon channel silicon is silicon particles filled in the porous carbon channels, wherein the particle size of the silicon particles is ≤30nm, the pore size of the porous carbon before filling with silicon particles is 2-5nm, and the filling rate of silicon particles in the porous carbon channels is >90%.
[0038] According to the present invention, preferably, in the mixture of graphite interlayer silicon and porous carbon channel silicon in step S3-1, the mass ratio of graphite interlayer silicon to porous carbon channel silicon is (1-5):(1-5), more preferably (1-2):(1-2), and even more preferably 1:1.
[0039] In this invention, the organic solution containing carbon nanotubes is an ethanol solution containing carbon nanotubes (CNTs).
[0040] According to the present invention, preferably, step S3-2: In the soft carbon layer coating: The gas used for coating the soft carbon layer is a mixture of ethylene and nitrogen, and the volume content of ethylene is 5-20 vol% based on the total volume of the mixture. The soft carbon layer is coated at a temperature of 600-800℃ for 30-120 minutes.
[0041] According to the present invention, preferably, step S3-2: In the hard carbon layer coating: The gas used for coating the hard carbon layer is a mixture of benzene and acetylene, and the volume ratio of benzene to acetylene is 1:(1-4). The hard carbon layer is coated at a temperature of 750-900℃ for 60-150 minutes.
[0042] According to the present invention, preferably, step S3-2: In the graphite layer coating: The gas used for coating the graphite layer is a mixture of methane, hydrogen, and nitrogen, with the methane volume content being 10-40 vol% and the hydrogen volume content being 10-20 vol%. The graphite layer is coated at a temperature of 850-1050℃ for 15-60 minutes.
[0043] In this invention, the soft carbon layer coating, hard carbon layer coating, and graphite layer coating are performed by placing the conductive bridge network in a multi-temperature zone rotary furnace and sequentially passing it through three independent temperature control zones to continuously coat the three types of carbon layers, with each zone isolated by a protective gas.
[0044] Table 9 Soft carbon layer coating, hard carbon layer coating, graphite layer coating
[0045] According to the present invention, preferably, The thickness of the soft carbon layer is 8-12 nm, and the intensity ratio of its Raman spectrum D peak to G peak is >1.2; The thickness of the hard carbon layer is 12-18 nm, and the intensity ratio of its Raman spectrum D peak to G peak is 0.8-0.9. The graphite layer has a thickness of 4-6 nm, and the intensity ratio of its Raman spectrum D peak to G peak is ≤0.3.
[0046] In another aspect, the present invention provides a method for preparing the interlayer-pore synergistic silicon-carbon composite anode material, resulting in an interlayer-pore synergistic silicon-carbon composite anode material.
[0047] The beneficial effects of the technical solution of this invention are as follows: This invention proposes a dual-phase carrier composite structure, which combines the technical advantages of graphite interlayer deposition and porous carbon channel deposition to achieve a balance of high capacity, low expansion, and high initial efficiency, providing core material support for the next generation of high-energy-density lithium-ion batteries, as detailed below: 1. Dual-phase carrier structure design: This invention is a synergistic composite of graphite interlayer silicon (Si@G, silicon particles embedded in graphite sheets, wherein the silicon particle size is 20-50 nm, and the interlayer spacing of the graphite sheets after silicon particle embedding is 0.45-0.55 nm) and porous carbon channel silicon (Si@PC, silicon particles filling porous carbon channels, wherein the silicon particle size is ≤30 nm, the pore size of the porous carbon before silicon particle filling is 2-5 nm, and the silicon particle filling rate in the porous carbon channels is >90%). The graphite phase provides a conductive network, and the porous carbon phase carries high capacity, achieving decoupling of conductivity and silicon loading for the first time.
[0048] 2. Gradient temperature deposition process: This invention uses plasma pretreatment-low temperature deposition (nucleation)-gradient temperature rise to high temperature deposition (filling) in the preparation of silicon between graphite layers, which can precisely control the particle size of silicon particles between graphite layers to 20-50nm and the interlayer filling rate >92%.
[0049] 3. Dual-stage pore closure and pore optimization: This invention employs a dual-stage pore closure pretreatment—hydrogen plasma activation—during the preparation of porous carbon-silicon, which can seal the ineffective micropores of the porous carbon support, thereby reducing its specific surface area by 25%, and thus increasing the silane utilization rate to 92%. Ultimately, this improves the first-stage efficiency of batteries prepared using the silicon-carbon composite anode material of this invention by 5-8 percentage points.
[0050] 4. Three-gradient functionalized carbon coating: This invention achieves the effect of soft carbon buffering stress, hard carbon mechanical constraint, and graphitized carbon conductivity + electrolyte barrier through the design of inner soft carbon-middle hard carbon-outer graphitized carbon, which synergistically inhibits expansion (the electrode expansion rate of the half cell prepared by the silicon-carbon composite anode material in Example 1 is 11.8%).
[0051] 5. Interface bridging technology: This invention introduces carboxylated CNTs between Si@G and Si@PC particles to form Si-OC chemical bonds (connected by carbon nanotube network bridging), which increases the silicon-carbon interface strength from 35MPa (Comparative Example 1) to 152MPa (Example 1) and reduces the crack propagation rate by 85% (Example 1 compared to Comparative Example 1).
[0052] 6. The lithium-ion battery prepared using the silicon-carbon composite anode material of the present invention meets the following requirements: full cell energy density ≥350Wh / kg, half cell capacity retention rate ≥87.5% after 1000 half cell cycles, and full-charge electrode expansion rate ≤15% after 100 half cell cycles.
[0053] Other features and advantages of the present invention will be described in detail in the following detailed description section. Detailed Implementation
[0054] Preferred embodiments of the invention will now be described in more detail. While preferred embodiments of the invention are described below, it should be understood that the invention can be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that the invention will be thorough and complete, and will fully convey the scope of the invention to those skilled in the art.
[0055] Example 1
[0056] This embodiment provides a method for preparing a silicon-carbon composite anode material with interlayer-pore synergy, the preparation method comprising the following steps: Step S1: Preparation of Si@G S1-1: After placing the graphite matrix (artificial graphite with D50=15μm) in the first reactor, the first reactor is evacuated (until the gas pressure inside the first reactor is 10Pa) and an argon-oxygen mixture is introduced (the volume ratio of Ar to O2 is 9:1, the inlet flow rate of the argon-oxygen mixture is 2L / min, and the steady-state working pressure of the first reactor after the argon-oxygen mixture is introduced is ≤50Pa) to perform plasma pretreatment (the output power of the radio frequency power supply is 300W, and the plasma pretreatment time is 10min).
[0057] S1-2: After the plasma pretreatment is completed, a mixture of silicon source gas is introduced into the first reactor to perform low-temperature deposition, gradient heating and high-temperature deposition treatment in sequence. In the low-temperature deposition process: the first silicon source gas mixture is a mixture of SiH4 and Ar, and the volume content of SiH4 is 5 vol% based on the total volume of the SiH4+Ar mixture; the inlet flow rate of the SiH4+Ar mixture is 2 L / min; the temperature of the low-temperature deposition process is 550℃, and the time is 60 min; the steady-state working pressure of the first reactor after the SiH4+Ar mixture is introduced is 0.3 MPa. In the gradient heating process: the heating rate is 2℃ / min; In the high-temperature deposition process: the first silicon source gas mixture is a mixture of SiH4 + Ar + H2, and based on the total volume of the SiH4 + Ar + H2 mixture, the volume content of SiH4 is 15 vol%, and the volume content of hydrogen is 5 vol%; the inlet flow rate of the SiH4 + Ar + H2 mixture is 2 L / min; the temperature of the high-temperature deposition process is 650℃, and the time is 120 min; the steady-state working pressure of the first reactor after the SiH4 + Ar + H2 mixture is introduced is 0.1 MPa.
[0058] S1-3: After the high-temperature deposition process is completed, the first reactor is cooled to room temperature of 25°C under a nitrogen atmosphere (cooling rate of 5°C / min). During this period, a mixed gas containing passivating gas is introduced into the first reactor for cooling and passivation treatment for 30 minutes to obtain graphite interlayer silicon. The passivating gas mixture is an Ar+C2H4 mixture, and the C2H4 volume content is 1 vol% based on the total volume of the Ar+C2H4 mixture; the inlet flow rate of the passivating gas mixture is 2 L / min. The interlayer silicon in the graphite consists of silicon particles embedded in graphite sheets, wherein the particle size of the silicon particles is 20-50 nm, the interlayer spacing of the graphite sheets after the silicon particles are embedded is 0.45-0.55 nm, and the interlayer filling rate is >92%.
[0059] Step S2: Preparation of Si@PC S2-1: A porous carbon matrix (BET=2000m) 2 After placing / g of coconut shell porous carbon into the second reactor, the second reactor is evacuated and then the first carbon source mixed gas is introduced in sequence to carry out a two-stage closed-pore pretreatment. In the first-stage closed-pore pretreatment: the first carbon source mixed gas is a mixture of C2H2 and N2, with a volume ratio of C2H2 to N2 of 1:5; the inlet flow rate of the C2H2+N2 mixed gas is 2L / min; the temperature of the first-stage closed-pore pretreatment is 680℃ and the time is 1h. In the secondary closed-pore pretreatment: the first carbon source mixed gas is a mixture of CH4 and H2, with a volume ratio of CH4 to H2 of 1:3; the inlet flow rate of the CH4+H2 mixed gas is 2 L / min; the temperature of the secondary closed-pore pretreatment is 750℃ and the time is 0.5 h.
[0060] S2-2: After the two-stage closed-hole pretreatment is completed, the second reactor is evacuated and argon-hydrogen mixed gas (H2 and Ar volume ratio is 4:1, argon-hydrogen mixed gas inlet flow rate is 2L / min, and steady-state working pressure of the second reactor after the argon-hydrogen mixed gas is introduced is 50Pa) to carry out hydrogen plasma activation treatment (RF power output power is 500W, hydrogen plasma activation treatment time is 20min).
[0061] S2-3: After the hydrogen plasma activation treatment is completed, a mixture of the second silicon source gas is introduced into the second reactor to perform low-temperature infiltration, medium-temperature nucleation and high-temperature filling treatment in sequence; In the low-temperature permeation treatment: the second silicon source gas mixture is a mixture of SiH4 and H2, and the volume content of SiH4 is 10 vol% based on the total volume of the SiH4+H2 mixture; the inlet flow rate of the SiH4+H2 mixture is 2 L / min; the temperature of the low-temperature permeation treatment is 650℃ and the time is 1 h. In the intermediate-temperature nucleation process: the second silicon source gas mixture is a mixture of SiH4 + H2 + HCl, and based on the total volume of the SiH4 + H2 + HCl mixture, the volume content of SiH4 is 20 vol%, and the volume content of HCl is 5 vol%; the inlet flow rate of the SiH4 + H2 + HCl mixture is 2 L / min; the temperature of the intermediate-temperature nucleation process is 750℃, and the time is 2 h; In the high-temperature filling process: the second silicon source gas mixture is a mixture of SiH4 and H2, and the volume content of SiH4 is 30 vol% based on the total volume of the SiH4+H2 mixture; the inlet flow rate of the SiH4+H2 mixture is 2 L / min; the temperature of the high-temperature filling process is 850°C and the time is 1 h.
[0062] S2-4: After the high-temperature filling treatment is completed, a second carbon source mixed gas (the second carbon source mixed gas is a C2H4+H2 mixture, and the volume content of C2H4 is 5 vol% based on the total volume of the C2H4+H2 mixture; the inlet flow rate of the C2H4+H2 mixture is 2 L / min) is introduced into the second reactor at 700°C for in-situ passivation treatment for 30 min to obtain porous carbon channel silicon; The porous carbon channel silicon consists of silicon particles filled within porous carbon channels, wherein the silicon particle size is ≤30nm, the pore size of the porous carbon before filling with silicon particles is 2-5nm, and the filling rate of silicon particles within the porous carbon channels is >90%.
[0063] Step S3: Preparation of interlayer-pore synergistic silicon-carbon composite anode material: S3-1: After mixing Si@G and Si@PC at a mass ratio of 1:1 (total silicon loading of 28wt%), spray 5mL / g of 1wt% CNTs-ethanol solution, stir, and dry at 60℃ to obtain a conductive bridge network.
[0064] S3-2: The conductive bridge network is placed in a multi-temperature zone rotary furnace and passed through three independent temperature control zones in sequence. The conductive bridge network is then coated with a soft carbon layer, a hard carbon layer, and a graphite layer by chemical vapor deposition (with 5L / min argon gas passing through each temperature zone for isolation) to obtain the interlayer-pore synergistic silicon-carbon composite anode material. In the soft carbon layer coating: the gas used for coating the soft carbon layer is a mixture of C2H4 and N2, and the volume content of C2H4 is 10 vol% based on the total volume of the C2H4 + N2 mixture; the coating temperature is 700℃ and the time is 60 min; the thickness of the soft carbon layer is 8-12 nm, and the intensity ratio of its Raman spectrum D peak to G peak is >1.2; In the hard carbon layer coating: the gas used for hard carbon layer coating is a mixture of C6H6 + C2H2 + N2, and the volume content of C6H6 is 5 vol% and the volume content of C2H2 is 5 vol% based on the total volume of the C6H6 + C2H2 + N2 mixture; the hard carbon layer coating temperature is 800℃ and the time is 90 min; the thickness of the hard carbon layer is 12-18 nm, and the intensity ratio of its Raman spectrum D peak to G peak is 0.8-0.9; In the graphite coating: the gas used for coating the graphite layer is a mixture of CH4+H2+N2, and the volume content of CH4 is 20 vol% and the volume content of H2 is 10 vol% based on the total volume of the CH4+H2+N2 mixture; the coating temperature is 900℃ and the time is 30 min; the thickness of the graphite layer is 4-6 nm, and the intensity ratio of its Raman spectrum D peak to G peak is ≤0.3.
[0065] Example 2
[0066] The only difference between this embodiment and Embodiment 1 is that: The low-temperature deposition treatment was carried out at a temperature of 500℃ for 120 minutes. The high-temperature deposition treatment was carried out at a temperature of 600℃ for 240 minutes. The temperature of the low-temperature permeation treatment is 600°C; The high-temperature filling process is carried out at a temperature of 800°C.
[0067] The temperature at which the soft carbon layer is coated is 600°C; The hard carbon layer coating time is 150 minutes.
[0068] Example 3 (High Silicon Capacity Type)
[0069] The only difference between this embodiment and Embodiment 1 is that: The mass ratio of Si@G to Si@PC is 1:2, and the total silicon loading is increased to 40wt%.
[0070] Comparative Example 1 (without coating)
[0071] The only difference between this comparative example and Example 1 is that Si@G and Si@PC are physically mixed at a mass ratio of 1:1 to obtain a silicon-carbon composite anode material (without interface bridging and any CVD coating).
[0072] Comparative Example 2 (Single-layer hard carbon coating)
[0073] The only difference between this comparative example and Example 1 is that the conductive bridge network is coated with only a hard carbon layer (without a soft carbon layer or a graphite layer), resulting in a silicon-carbon composite anode material. Furthermore, in the hard carbon layer coating: the gas used for the hard carbon layer coating is a mixture of C6H6 + C2H2 + N2, and the volume content of C6H6 is 5 vol% and the volume content of C2H2 is 5 vol% based on the total volume of the C6H6 + C2H2 + N2 mixture; the temperature of the hard carbon layer coating is 800℃ and the time is 150 min; the thickness of the hard carbon layer is 12-18 nm, and the intensity ratio of its Raman spectrum D peak to G peak is 0.8-0.9.
[0074] Comparative Example 3 (single porous carbon phase, no graphite phase)
[0075] The only difference between this comparative example and Example 1 is that: Without preparing Si@G, the Si@PC prepared in step S2 is directly subjected to the same steps S3-1 and S3-2 as in Example 1 to obtain the silicon-carbon composite anode material.
[0076] Comparative Example 4
[0077] This comparative example uses commercially available porous carbon CVD silicon-carbon anode material, SCC55™, purchased from Group14 Technologies, USA.
[0078] Test Example 1
[0079] This test example uses the negative electrode materials of the above embodiments and comparative examples to prepare coin half-cells, and tests are conducted on reversible capacity, capacity retention after 1000 cycles, capacity retention after 100 cycles, electrode expansion rate at full charge after 100 cycles, and ion diffusion coefficient.
[0080] in: Button half-cell assembly: CR2032 type, with lithium metal sheet as counter electrode, Celgard 2500 separator, and 1M LiPF6 in EC / EMC / DMC (volume ratio 1:1:1) electrolyte with 2% FEC added; the negative electrode material to be tested, conductive carbon black (SP), carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) are mixed in a mass ratio of 80:10:5:5 to form a slurry, which is then coated on a copper current collector to obtain the negative electrode sheet; Formation and cycling: 0.1C constant current and constant voltage charging to 2.0V (0.005C cutoff), 0.1C constant current discharging to 0.005V, and 1C / 1C cycling test; Expansion rate test: The battery was disassembled under full charge (charged to 2.0V), and the change in thickness of the negative electrode was measured. The formula is: Expansion rate = (thickness after cycling - initial thickness) / initial thickness × 100%; Ion diffusion coefficient: Tested using potentiostatic intermittent titration (PITT) and calculated according to Fick's second law.
[0081] The test results are shown in Table 10.
[0082] Table 10
[0083] Table 10 Half-cell performance analysis: 1. Example 1 showed a first-efficiency of 93.2%, which was 12.7% higher than Comparative Example 1, demonstrating that gradient coating (i.e., soft carbon layer coating, hard carbon layer coating and graphite layer coating, the same below) can reduce side reactions; 2. The expansion rate of Example 1 was only 11.8% (compared to 32.4% in Comparative Example 1), proving that the three-layer carbon shell obtained by gradient coating (soft carbon layer coating, hard carbon layer coating, and graphite layer coating) can suppress volume expansion. 3. The ion diffusion coefficient of Example 1 is 2.1 × 10⁻⁶. -10 cm 2 / s (2.6 times higher than the single-layer coating in Comparative Example 2), supporting fast charging performance; 4. After 1000 weeks, Example 1 maintained 87.5%, an increase of 17.4% compared to Comparative Example 4; 5. In the table, "N / A" indicates that this group could not complete the 1000-cycle test due to excessively rapid electrolyte consumption (limited electrolyte volume in the half-cell). In Examples 3 and 3, with higher silicon loading, the electrolyte was almost completely depleted and the internal resistance increased sharply after approximately 600-800 cycles, making further testing impossible. Those skilled in the art should understand that this phenomenon is an inherent limitation of high-capacity silicon-carbon materials in half-cell testing and does not affect the full disclosure of the technical solution.
[0084] Test Example 2
[0085] This test example uses the negative electrode materials of the above embodiments and comparative examples to prepare full cells, and tests are conducted on energy density and capacity retention after 1000, 800, 500, and 200 cycles.
[0086] in: The negative electrode materials obtained in the examples and comparative examples were combined with the NCM811 positive electrode (area capacity 4.8 mAh / cm²). 2 Matching was performed to prepare a 2.8Ah soft-pack battery cell; The negative electrode is in excess by 5% (N / P=1.05); The electrolyte is 1M LiPF6 in EC / EMC / DMC (volume ratio 1:1:1), with 10% FEC and 2% VC added; Formation process: 0.05C constant current charging to 4.2V, 0.2C constant current discharging to 2.75V, cycled 3 times; Cyclic test: 1C constant current and constant voltage charging to 4.2V (0.05C cutoff), 1C constant current discharging to 2.75V, repeated charging and discharging; test temperature: 25±2℃.
[0087] The test results are shown in Table 11.
[0088] Table 11
[0089] Table 11 Full Battery Performance Analysis: 1. First-efficiency and energy density 1) Example 1 has an initial efficiency of 89.5% and an energy density of 352Wh / kg, which is 6.5 percentage points higher than Comparative Example 4 (industry benchmark, 83.0%, 340Wh / kg) and 3.5% higher in energy density; 2) Example 3 (high silicon capacity type) has the highest energy density (370Wh / kg), but its first efficiency is slightly lower (84.5%), making it suitable for application scenarios that pursue the ultimate energy density; 3) Comparative Example 1 (uncoated) had a first-efficiency of only 76.0% and the lowest energy density (315Wh / kg), demonstrating that gradient coating makes a significant contribution to both first-efficiency and energy density.
[0090] 2. Cyclic stability
[0091] 1) Example 1 showed a capacity retention of up to 78.4% after 1000 cycles, which was far superior to Comparative Example 4 (63.3%), and the decay rate remained the lowest throughout the entire cycle. 2) Comparative Example 2 (single-layer hard carbon coating) had a retention rate of 65.2% after 1000 cycles, which was better than Comparative Example 4, but still lower than Example 1, proving that the three-gradient coating is irreplaceable in improving long-term cycling stability. 3) Example 3 (high silicon capacity type) had a 1000-cycle retention rate of 75.2%, which was higher than that of Comparative Example 3 (62.1%), indicating that under the same high silicon load, the introduction of graphite phase (two-phase structure) can significantly improve cycle stability; 4) Comparative Example 1 (uncoated) showed severe degradation (62.0%) after 500 weeks, and only 38.6% remained after 1000 weeks, verifying that silicon-carbon materials without protective layers cannot meet the requirements for practical application.
[0092] Test Example 3
[0093] This test example utilizes the negative electrode materials of the above embodiments and comparative examples to prepare coin half-cells and conducts interface bonding strength tests.
[0094] in: The button cell assembly is the same as in Test Example 1; After 50, 100, and 200 cycles at 1C magnification, the electrodes were disassembled and subjected to FIB-SEM cross-sectional analysis. The average length of internal cracks within the particles was calculated for each cycle number, and the slope of the linear fitting was used as the crack propagation rate (μm / cycle). The crack propagation rate (μm / cycle) was used to characterize the interface fatigue resistance. A Hysitron TI 950 nanoindenter was used to perform indentation tests on individual particles of the examples and comparative samples. The test conditions were: maximum load 500 μN, loading rate 50 μN / s, and holding time 5 s. The nanoindentation modulus and hardness at the silicon-carbon interface were calculated using the Oliver-Pharr method, and the crack propagation length was observed around the indentation using SEM.
[0095] The test results are shown in Table 12.
[0096] Table 12
[0097] Table 12 Analysis: The soft carbon buffer layer (elastic modulus 3-5 GPa) and the hard carbon confinement layer (compressive strength >200 MPa) in the gradient coating work together to increase the silicon-carbon interface strength of Example 1 to 152 MPa and reduce the crack propagation rate to 0.08 μm / week, which is far superior to the uncoated group (Comparative Example 1, 0.53 μm / week) and Comparative Example 3 (0.32 μm / week).
[0098] Test Example 4
[0099] This test example utilizes the negative electrode materials of the above-described embodiments and comparative examples to prepare full cells, and performs SEI film composition analysis.
[0100] in: The full battery assembly is the same as in Test Example 2; After the full cell (NCM811 / silicon-carbon anode) was cycled 100 times at 1C, it was disassembled in a glove box at full charge (4.2V). The anode sheet was cleaned with DMC (dimethyl carbonate) and then subjected to XPS (X-ray photoelectron spectroscopy) for in-depth analysis.
[0101] The test results are shown in Table 13.
[0102] Table 13
[0103] Table 13 Analysis: 1. The SEI film in Example 1 is thin and rich in LiF (high ionic conductivity). 2. In Comparative Example 1, the organic component content of the uncoated group was as high as 41.2% (high impedance).
[0104] In summary: 1. Two-phase carrier (interlayer silicon in graphite + porous carbon channel silicon): It achieves the synergy of a highly conductive framework and a high-capacity host. The reversible capacity of Example 1 with 28wt% silicon loading reaches 522mAh / g, and that of Example 3 with 40wt% silicon loading reaches 1780mAh / g. 2. Three-gradient carbon coating (soft carbon-hard carbon-graphite carbon): reduced the volume expansion rate from 32.4% (Comparative Example 1 without coating) to 11.8% in Example 1, and increased the capacity retention rate after 1000 cycles from 70.1% (Comparative Example 4) to 87.5% in Example 1; 3. Interface bridging (CNTs + chemical bonding): Increased the silicon-carbon interface strength from 35 MPa to 152 MPa, and reduced the crack propagation rate by 85%; 4. Overall performance: Example 1 surpasses Comparative Example 4 in all three core indicators: first efficiency, energy density, and capacity retention rate after 1000 cycles, achieving a balance of high capacity, low expansion, and long life.
[0105] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.
Claims
1. A method for preparing a silicon-carbon composite anode material with interlayer-pore synergy, characterized in that, The preparation method includes the following steps: S1-1: After placing the graphite substrate in the first reactor, the first reactor is evacuated and then argon-oxygen mixed gas is introduced in sequence for plasma pretreatment. S1-2: After the plasma pretreatment is completed, a mixture of silicon source gas is introduced into the first reactor to perform low-temperature deposition, gradient heating and high-temperature deposition treatment in sequence. S1-3: After the high-temperature deposition process is completed, the first reactor is gradually cooled under a protective atmosphere and a mixed gas containing passivating gas is introduced into the first reactor for cooling and passivation treatment to obtain graphite interlayer silicon. S2-1: After placing the porous carbon matrix in the second reactor, the second reactor is evacuated and then a first carbon source mixed gas is introduced in sequence to perform a two-stage closed-pore pretreatment. S2-2: After the two-stage closed-hole pretreatment is completed, the second reactor is evacuated and argon-hydrogen mixed gas is introduced in sequence to carry out hydrogen plasma activation treatment. S2-3: After the hydrogen plasma activation treatment is completed, a mixture of the second silicon source gas is introduced into the second reactor to perform low-temperature infiltration, medium-temperature nucleation and high-temperature filling treatment in sequence; S2-4: After the high-temperature filling process is completed, a second carbon source mixed gas is introduced into the second reactor to perform in-situ passivation treatment and obtain porous carbon channel silicon. S3-1: Spray an organic solution containing carbon nanotubes into the mixture of graphite interlayer silicon and porous carbon channel silicon, stir and dry to obtain a conductive bridge network. S3-2: The conductive bridge network is sequentially coated with a soft carbon layer, a hard carbon layer, and a graphite layer using chemical vapor deposition to obtain the interlayer-channel synergistic silicon-carbon composite anode material.
2. The method for preparing the interlayer-pore synergistic silicon-carbon composite anode material according to claim 1, wherein, The graphite matrix is at least one of artificial graphite, flake graphite, and mesophase carbon microspheres; the particle size of the graphite matrix is 5-50 μm; In the plasma pretreatment: The volume ratio of argon to oxygen in the argon-oxygen mixture is (8-95):1; the inlet flow rate of the argon-oxygen mixture is 0.5-5 L / min. The output power of the radio frequency power supply for plasma pretreatment is 100-1000W; The plasma pretreatment time is 5-30 minutes; The steady-state working pressure of the first reactor after the argon-oxygen mixture is introduced is 1-50 Pa.
3. The method for preparing the interlayer-pore synergistic silicon-carbon composite anode material according to claim 1, wherein, In the aforementioned low-temperature deposition process: The first mixture containing silicon source gas is a mixture of silicon source gas and argon gas, and the volume content of silicon source gas is 1-10 vol% based on the total volume of the mixture of silicon source gas and argon gas; the inlet flow rate of the first mixture containing silicon source gas is 0.5-5 L / min. The low-temperature deposition treatment is performed at a temperature of 500-600℃ for a time of 30-120 minutes. The steady-state working pressure of the first reactor after the first mixture containing silicon source gas is introduced is 0.1-0.8 MPa; In the gradient heating process, the heating rate is 1-5℃ / min; In the aforementioned high-temperature deposition process: The first mixture containing silicon source gas is a mixture of silicon source gas, hydrogen and argon, and based on the total volume of the mixture, the volume content of silicon source gas is 10-25 vol%, and the volume content of hydrogen is 0-15 vol%; the inlet flow rate of the first mixture containing silicon source gas is 0.5-5 L / min. The high-temperature deposition treatment is performed at a temperature of 600-750℃ for a time of 60-240 minutes. The steady-state working pressure of the first reactor after the first mixture containing silicon source gas is introduced is 0.05-0.5 MPa; The silicon source gases used in the low-temperature deposition process and the high-temperature deposition process are each independently at least one of SiH4, SiH4, Si2H6, SiCl4, SiHCl3 and SiH2Cl2.
4. The method for preparing the interlayer-pore synergistic silicon-carbon composite anode material according to claim 1, wherein, In the cooling passivation process: The cooling rate of the gradient cooling is 1-15℃ / min, and the final temperature of the gradient cooling is 20-30℃. The passivating gas mixture is a mixture of argon and ethylene, and the volume content of ethylene is 0.5-5 vol% based on the total volume of the argon and ethylene mixture; the inlet flow rate of the passivating gas mixture is 0.5-5 L / min. The interlayer silicon in the graphite consists of silicon particles embedded in graphite sheets, wherein the particle size of the silicon particles is 20-50 nm, and the interlayer spacing of the graphite sheets after the silicon particles are embedded is 0.45-0.55 nm.
5. The method for preparing the interlayer-pore synergistic silicon-carbon composite anode material according to claim 1, wherein, The porous carbon matrix is coconut shell-based porous carbon and / or rice husk-based porous carbon; the BET specific surface area of the porous carbon matrix is 1500-2500 m². 2 / g; In the aforementioned two-stage closed-cell pretreatment: The pressure inside the second reactor is ≤50Pa after evacuation. The two-stage closed-pore pretreatment includes a first-stage closed-pore pretreatment and a second-stage closed-pore pretreatment performed sequentially. In the first-stage closed-cell pretreatment: The first carbon source mixture is a mixture of acetylene and nitrogen, with a volume ratio of acetylene to nitrogen of 1:(2-10); the inlet flow rate of the first carbon source mixture is 0.5-5 L / min. The temperature of the first-stage closed-cell pretreatment is 600-750℃, and the time is 0.5-3h; In the secondary closed-cell pretreatment: The first carbon source mixture is a mixture of methane and hydrogen, with a volume ratio of methane to hydrogen of 1:(1-5); the inlet flow rate of the first carbon source mixture is 0.5-5 L / min. The temperature of the secondary closed-pore pretreatment is 700-850℃, and the time is 0.2-1.5h.
6. The method for preparing the interlayer-pore synergistic silicon-carbon composite anode material according to claim 1, wherein, In the hydrogen plasma activation treatment: The volume ratio of argon to hydrogen in the argon-hydrogen mixture is 1:(1-9); the inlet flow rate of the argon-hydrogen mixture is 0.5-5 L / min. The output power of the radio frequency power supply for hydrogen plasma activation treatment is 100-1000W; The hydrogen plasma activation treatment time is 5-60 min; The steady-state working pressure of the second reactor after the argon-hydrogen mixture is introduced is 20-100 Pa.
7. The method for preparing the interlayer-pore synergistic silicon-carbon composite anode material according to claim 1, wherein, In the aforementioned low-temperature permeation treatment: The second mixture containing silicon source gas is a mixture of silicon source gas and hydrogen, and the volume content of silicon source gas is 5-15 vol% based on the total volume of the mixture of silicon source gas and hydrogen; the inlet flow rate of the second mixture containing silicon source gas is 0.5-5 L / min. The low-temperature permeation treatment is performed at a temperature of 600-700℃ for a time of 0.5-2 hours. In the mesophilic nucleation process: The second mixture containing silicon source gas is a mixture of silicon source gas, hydrogen chloride, and hydrogen, and based on the total volume of the mixture of silicon source gas, hydrogen chloride, and hydrogen, the volume content of silicon source gas is 15-25 vol%, and the volume content of hydrogen chloride is 2-8 vol%; the inlet flow rate of the second mixture containing silicon source gas is 0.5-5 L / min. The intermediate-temperature nucleation treatment is performed at a temperature of 700-800℃ for 1-3 hours. In the high-temperature filling process: The second mixture containing silicon source gas is a mixture of silicon source gas and hydrogen, and the volume content of silicon source gas is 25-40 vol% based on the total volume of the mixture of silicon source gas and hydrogen; the inlet flow rate of the second mixture containing silicon source gas is 0.5-5 L / min. The high-temperature filling treatment is carried out at a temperature of 800-900℃ for a time of 0.5-2 hours. The silicon source gases used in the low-temperature infiltration treatment, the medium-temperature nucleation treatment, and the high-temperature filling treatment are each independently at least one of SiH4, SiH4, Si2H6, SiCl4, SiHCl3, and SiH2Cl2.
8. The method for preparing the interlayer-pore synergistic silicon-carbon composite anode material according to claim 1, wherein, In the in-situ passivation process: The second carbon source mixture is a mixture of ethylene and hydrogen, and the volume content of ethylene is 2-10 vol% based on the total volume of the mixture of ethylene and hydrogen; the inlet flow rate of the second carbon source mixture is 0.5-5 L / min. The in-situ passivation treatment is performed at a temperature of 650-800℃ for 15-90 minutes. The porous carbon channel silicon consists of silicon particles filled within porous carbon channels, wherein the silicon particle size is ≤30nm, the pore size of the porous carbon before filling with silicon particles is 2-5nm, and the filling rate of silicon particles within the porous carbon channels is >90%.
9. The method for preparing the interlayer-pore synergistic silicon-carbon composite anode material according to claim 1, wherein, In the mixture of graphite interlayer silicon and porous carbon channel silicon in step S3-1, the mass ratio of graphite interlayer silicon to porous carbon channel silicon is (1-5):(1-5). Step S3-2: In the soft carbon layer coating: The gas used for coating the soft carbon layer is a mixture of ethylene and nitrogen, and the volume content of ethylene is 5-20 vol% based on the total volume of the mixture. The soft carbon layer is coated at a temperature of 600-800℃ for 30-120 minutes. In the hard carbon layer coating: The gas used for coating the hard carbon layer is a mixture of benzene and acetylene, and the volume ratio of benzene to acetylene is 1:(1-4). The hard carbon layer is coated at a temperature of 750-900℃ for 60-150 minutes. In the graphite layer coating: The gas used for coating the graphite layer is a mixture of methane, hydrogen, and nitrogen, with the methane volume content being 10-40 vol% and the hydrogen volume content being 10-20 vol%. The graphite layer is coated at a temperature of 850-1050℃ for 15-60 minutes. The thickness of the soft carbon layer is 8-12 nm, and the intensity ratio of its Raman spectrum D peak to G peak is >1.2; The thickness of the hard carbon layer is 12-18 nm, and the intensity ratio of its Raman spectrum D peak to G peak is 0.8-0.
9. The graphite layer has a thickness of 4-6 nm, and the intensity ratio of its Raman spectrum D peak to G peak is ≤0.
3.
10. The interlayer-pore synergistic silicon-carbon composite anode material prepared by the preparation method of any one of claims 1-9.